Genome-Wide Characterization and Expression Analysis of Soybean TGA Transcription Factors Identified a Novel TGA Gene Involved in Drought and Salt Tolerance - Li, Bo; Liu, Ying; Cui, Xi-Yan; Fu, Jin-Dong; Zhou, Yong-Bin; Zheng, Wei-Jun; Lan, Jin-Hao; Jin, Long-Guo; Chen, Ming; Ma, You-Zhi; Xu, Zhao-Shi; Min, Dong-Hong (Frontiers in Plant Science, 2019)
The TGA transcription factors, a subfamily of bZIP group D, play crucial roles in various biological processes, including the regulation of growth and development as well as responses to pathogens and abiotic stress. In this study, 27 TGA genes were identified in the soybean genome. The expression patterns of GmTGA genes showed that several GmTGA genes are differentially expressed under drought and salt stress conditions. Among them, GmTGA17 was strongly induced by both stress, which were verificated by the promoter-GUS fusion assay. GmTGA17 encodes a nuclear-localized protein with transcriptional activation activity. Heterologous and homologous overexpression of GmTGA17 enhanced tolerance to drought and salt stress in both transgeinc Arabidopsis plants and soybean hairy roots. However, RNAi hairy roots silenced for GmTGA17 exhibited an increased sensitivity to drought and salt stress. In response to drought or salt stress, transgenic Arabidposis plants had an increased chlorophyll and proline contents, a higher ABA content, a decreased MDA content, a reduced water loss rate, and an altered expression of ABA- responsive marker genes compared with WT plants. In addition, transgenic Arabidposis plants were more sensitive to ABA in stomatal closure. Similary, measurement of physiological parameters showed an increase in chlorophyll and proline contents, with a decrease in MDA content in soybean seedlings with overexpression hairy roots after drought and salt stress treatments. The opposite results for each measurement were observed in RNAi lines. This study provides new insights for functional analysis of soybean TGA transcription factors in abiotic stress